Autoimmune pancreatitis in an adolescent female following dengue fever: a diagnostic challenge in IgG4-related disease - J. P., Sanjana; Aruldas, Anis Preethi; Anbalagan, Viknesh Prabu (International Journal of Research in Medical Sciences, 2025)
Autoimmune pancreatitis (AIP), a rare form of chronic pancreatitis, is often misdiagnosed due to its overlap with other causes of pancreatic inflammation. We report an unusual case of an 18-year-old female who developed acute pancreatitis in the context of dengue fever. Persistent elevation of pancreatic enzymes and characteristic imaging led to further evaluation, confirming Type 1 AIP through elevated serum IgG4, weakly positive ANA, and histopathology. This case emphasizes the need for a comprehensive diagnostic approach to avoid delayed diagnosis and prevent irreversible organ damage.